Influence of extraction process on antioxidant activity and rutin content in Physalis peruviana calyces extract - Maria Isabel Cardona, Reina Marcela Toro, Geison M. Costa, Luis Fernando Ospina, Leonardo Castellanos, Freddy A. Ramos, Diana Marcela Aragón (Journal of Applied Pharmaceutical Science, 2017)
Physalis peruviana is an exotic fruit highly valued for its bioactive compounds. This work evaluates the effect of some variables of the extraction process of P. peruviana calyces extract (considered waste material) on total phenolic content, rutin content, and in vitro antioxidant activity of the extracts obtained. First, the influence of certain factors of the extraction process on the above mentioned response variables were analyzed. The response variables were then evaluated using in vitro assays such as NO (nitric oxide) and DPPH (1,1-diphenyl-2- picrylhydrazyl) uptake for antioxidant activity; the Folin-Ciocalteu method for total phenolic content; and the external standard method by HPLC-DAD for quantification of rutin. The results showed that the optimal conditions needed to obtain the best results for the response variables evaluated are the use of ethanol 70% as extraction solvent, and a percolation time of 72 hours, these being the factors that positively influenced the results.
Keywords: Physalis peruviana, antioxidant activity, rutin, DPPH, HPLC-DAD.